2011
DOI: 10.1021/bi200777j
|View full text |Cite
|
Sign up to set email alerts
|

A Biochemical–Biophysical Study of Hemoglobins from Woolly Mammoth, Asian Elephant, and Humans

Abstract: This study is aimed at investigating the molecular basis of environmental adaptation of woolly mammoth hemoglobin (Hb) to the harsh thermal conditions of the Pleistocene Ice-ages. To this end, we have carried out a comparative biochemical-biophysical characterization of the structural and functional properties of recombinant hemoglobins (rHb) from woolly mammoth (rHb WM) and Asian elephant (rHb AE) in relation to human hemoglobins Hb A and Hb A2 (a minor component of human Hb). We have obtained oxygen equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…As reported previously (10), the Hill coefficients for rHb WM and rHb AE are lower than those of Hb A under all experimental conditions, suggesting a difference in the cooperativity of the oxygenation process for these Hbs (for details, see Supporting Information Figure 2S). The n 50 values for the mutants rHb WM (β/δQ101E), rHb WM (αN5K, β/δQ101E), and rHb WM (β/δQ101K), are maintained around the expected value of 1.8–2.5 in the range of pH 5.8–8.4 in 0.1 M MES or NaPi buffer, while the n 50 values for rHb WM (β/δQ101D) and rHb WM (αN5K, β/δA12T, β/δS86A) are found to be lower (1.0–2.0) under the same experimental conditions.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…As reported previously (10), the Hill coefficients for rHb WM and rHb AE are lower than those of Hb A under all experimental conditions, suggesting a difference in the cooperativity of the oxygenation process for these Hbs (for details, see Supporting Information Figure 2S). The n 50 values for the mutants rHb WM (β/δQ101E), rHb WM (αN5K, β/δQ101E), and rHb WM (β/δQ101K), are maintained around the expected value of 1.8–2.5 in the range of pH 5.8–8.4 in 0.1 M MES or NaPi buffer, while the n 50 values for rHb WM (β/δQ101D) and rHb WM (αN5K, β/δA12T, β/δS86A) are found to be lower (1.0–2.0) under the same experimental conditions.…”
Section: Resultssupporting
confidence: 83%
“…Experiments were conducted in the presence and absence of 0.5 mM inositol hexaphosphate (IHP), in the pH range 5.5 to 8.5. For these measurements, the rHbs were kept at 100–120 μM (in terms of heme) to minimize tetramer-dimer dissociation (10). Each sample was checked before and after measurements for met-hemoglobin (met-Hb) in a spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, while the molecular bases of some phenotypic traits have been identified, these studies generally are limited to a few wellcharacterized genes and pathways with relatively simple and direct genotype-phenotype relationships (Chan et al, 2010;Hoekstra et al, 2006;Lang et al, 2012;Smith et al, 2013;Storz et al, 2009). Previous structural and functional studies, for example, have shown that amino acid polymorphisms in the woolly mammoth hemoglobin b/d fusion gene (HBB/HBD) reduce oxygen affinity (Campbell et al, 2010;Yuan et al, 2011Yuan et al, , 2013, whereas amino acid polymorphisms in both the woolly mammoth and Neandertal melanocortin 1 receptor (MC1R) genes were hypomorphic compared to the ancestral alleles Rö mpler et al, 2006). Most traits, however, have complex genotype-phenotype relationships with phenotypic divergence arising through the accumulation of numerous variants of small individual effects rather than one or a few mutations of large effect.…”
Section: Introductionmentioning
confidence: 99%